Mahkota Dewa (Phaleria macrocarpa) Fruit Extract Decrease Malondialdehyde, Tumor Necrosis Factor-α, and Caspase 3 Levels May Improve Infertility in Endometriosis Mice - Brahmana, Ivanna Beru; Soetrisno, Soetrisno; Purwanto, Bambang; Pamungkasari, Eti Poncorini; Wasita, Brian; Budihastuti, Uki Retno; Pangestu, Mulyoto; Cempaka, Rita; Lestariningsih, Sri; Wulandari, Eka Tri; Maesaroh, Siti (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Endometriosis, which often causes infertility, is characterized by a complex interplay between oxidative stress, inflammatory response, and apoptosis. Currently, the most effective therapy used for endometriosis is hormonal treatments, however it has many common side effects. Therefore, it is necessary to explore alternative treatments for endometriosis, including herbal ingredients. Phaleria macrocarpa fruit contains flavonoids with strong antioxidant and anti-inflammatory properties which have potency to improve fertility in endometriosis cases. However, assessments of whether P. macrocarpa might have any effect on oxidative stress, inflammatory response, and apoptosis in relation to endometriosis are still limited. This study was conducted to identify the effect of P. macrocarpa fruit ethanol extract (PMFEE) in improving infertility by assessing oxidative stress, inflammatory response, and apoptosis parameters in endometriosis mice model.METHODS: Female Balb/C mice were endometriosis-induced, and treated either with 6.5 µg/day Letrozole, 7.5 mg/kgBW/day PMFEE, or 15 mg/kgBW/day PMFEE for 14 days. Heatlhy mice were also included as control. Mice were necropsied, then the uterus and fat tissue around the uterus was collected. Malondialdehyde (MDA) as oxidative stress marker, tumor necrosis factor (TNF)-α as inflammatory marker, and Caspase-3 as apoptosis marker were assessed using enzyme-linked immunosorbent assay (ELISA).RESULTS: In uterus, MDA and TNF-α levels were significantly different among all groups (p<0.05). PMFEE both at 7.5 and 15 mg/kgBW/day lowered MDA and TNF-α compared to the healthy mice and mice receiving Letrozol. Meanwhile, Caspase-3 levels were quite indifferent among groups, showing that PMFEE was able to maintain the Caspase-3 levels in the endometriosis-induced mice.CONCLUSION: PMFEE reduces the MDA and TNF-α, also maintains Caspase-3 levels in the uterus of endometriosis-induced mice, suggesting it might have potential to improve fertility in endometriosis mice.KEYWORDS: Phaleria macrocarpa, endometriosis, infertility, MDA, TNF-α, Caspase-3